Effect of Temperature Variations Gelatinizing of Biodegradable Plastic Starch Porang (Amorphophallus Oncophyllus) with Glycerol Plasticizers on Its Characterization - Sudiati, Sudiati; Maghfirah, Awan; Sofyan, Muhammad Zaidun; Syafira, Ridha; Mitri, Ayu (International Conference on Sciences Development and Technology, 2022)
The development of plastic polymers is widely used in the food and non-food industries, biodegradable plastics derived from porang starch into environmentally friendly plastics. Plastics are made by adding chitosan and adding a 60% glycerol plasticizer by varying the gelatinizing temperature in the manufacturing process. The gelatinization temperature was used in the process when the starch granule was heated by adding chitosan and glycerol so that the development of starch granules expand and produced a viscous liquid to provide the desired solution quality. The variations in the gelatinization temperature used are temperatures of 70 ˚C, 80 ˚C, and 90 ˚C, then mechanical, physical and characterization tests were carried out on biodegradable plastics. The effect of the gelatinization temperature of biodegradable plastics on the strong value of Tensile is getting lower the temperature, the higher the tensile strength value until it reaches a value of 0.7034 Mpa and at the elongation value which decreases with the higher the gelatinization temperature. The highest elongation value was 124.96% at a gelatinizing temperature of 70 ˚C. Meanwhile, the degradation test showed a decrease in mass every week and began to degrade in the fourth week, which took 28 days. SEM analysis of biodegradable plastics showed that there are white parts that clump together, because the glycerol plasticizer has a thick texture so that it is not dissolved evenly. The spectra results showed no change in the wave number of the FT- IR spectrum of the starch, chitosan, and glycerol spectrums with O-H, C-H, and N-H functional groups.